Studi Eksploratif Tentang Peran Struktur Organisasi Dalam Implementasi Strategi di PT. Mayora Indah Tbk - Muhonis, Daniel Ananda; Hariyantob, Bryan Michael; Sabrina , Salya Widya; Ramadhan, Yanuar (CV. ITTC INDONESIA, 2025)
The problem in this study stems from the strategic challenges faced by large companies such as PT Mayora Indah Tbk in ensuring that the organizational structure is capable of effectively supporting strategy implementation. The complex organizational structure, involving many work units, often becomes a barrier to cross-division collaboration and swift decision-making. This study aims to investigate how the organizational structure at PT Mayora Indah Tbk supports the implementation of corporate strategy, as well as how internal organizational members perceive the effectiveness of the structure. The research method used is a qualitative approach with documentation techniques applied to 15 internal and external documents, such as annual reports, strategic plans, SOPs, and organizational charts. Data analysis was conducted using thematic content analysis, supported by the theoretical framework of Miles & Snow (2023). The results show that the semi-decentralized organizational structure implemented by PT Mayora Indah Tbk is able to combine operational flexibility with strategic control. The delegation of authority to key divisions such as marketing and product development enables a quick response to market dynamics without losing strategic direction from the center. Formal coordination systems through ERP and cross-division forums also strengthen the alignment between strategy and operations. Thus, the organizational structure at PT Mayora Indah Tbk has proven effective in bridging strategic vision with practical implementation.